Development of novel LP1-based analogues with enhanced delta opioid receptor profile. Issue 17 (1st September 2017) - Pasquinucci, Lorella; Turnaturi, Rita; Prezzavento, Orazio; Arena, Emanuela; Aricò, Giuseppina; Georgoussi, Zafiroula; Parenti, Rosalba; Cantarella, Giuseppina; Parenti, Carmela
Graphical abstract: Highlights: Synthesis of LP1 analogues with different N -substituents. Compounds6, 7 and9 retained MOR but improved DOR affinity. Identification of MOR/DOR agonists assessed by GPI and MVD functional assays. Antinociception effects were assessed for compounds6, 7 and9 by tail flick test. The N -substituent nature maintains the LP1 MOR profile but improved the DOR profile. Abstract: Pain relief achieved by co-administration of drugs acting at different targets is more effective than that obtained with conventional MOR selective agonists usually associated to relevant side effects. It has been demonstrated that simultaneously targeting different opioid receptors is a more effective therapeutic strategy. Giving the promising role for DOR in pain management, novel LP1-based analogues with different N -substituents were designed and synthesized with the aim to improve DOR profile. For this purpose, we maintained the phenyl ring in the N -substituent of 6, 7-benzomorphan scaffold linked to an ethyl spacer bearing a hydroxyl/methyl or methoxyl group at carbon 2 or including it in a 1, 4-benzodioxane ring. LP1 analogues were tested by competition binding assays. Compounds6 (Ki MOR  = 2.47 nM, Ki DOR  = 9.6 nM), 7 (Ki MOR  = 0.5 nM and Ki DOR  = 0.8 nM) and9 (Ki MOR  = 1.08 nM, Ki DOR  = 6.6 nM) retained MOR affinity but displayed an improved DOR binding capacity as compared to LP1 (Ki MOR  = 0.83 nM, Ki DOR  = 29.1 nM). Moreover, GPI and MVD functional assays indicated that compounds6 (IC50  = 49.2 and IC50  = 10.8 nM), 7 (IC50  = 9.9 and IC50  = 11.8 nM) and9 (IC50  = 21.5 and IC50  = 4.4 nM) showed a MOR/DOR agonist profile, unlike LP1 that was a MOR agonist/DOR antagonist (IC50  = 1.9 and IC50  = 1240 nM). Measurements of their antinociceptive effect was evaluated by mice radiant tail flick test displaying for compounds6, 7 and9 ED50 values of 1.3, 1.0 and 0.9 mg/kg, i.p., respectively. Moreover, the antinociceptive effect of compound9 was longer lasting with respect to LP1. In conclusion the N -substituent nature of compounds6, 7 and9 shifts the DOR profile of LP1 from antagonism to agonism.